Organosulfur model compounds relevant to fossil fuels. (2nd March 2016) - Tang, Weijuan; Sheng, Huaming; Jin, Chunfen; Riedeman, James S.; Kenttämaa, Hilkka I.
Abstract : RATIONALE: The chemistry of desulfurization involved in processing crude oil is greatly dependent on the forms of sulfur in the oil. Sulfur exists in different chemical bonding environments in fossil fuels, including those in thiophenes and benzothiophenes, thiols, sulfides, and disulfides. In this study, the fragmentation behavior of the molecular ions of 17 aromatic organosulfur compounds with various functionalities was systematically investigated by using high‐resolution tandem mass spectrometry. METHODS: Multiple‐stage tandem mass spectrometric experiments were carried out using a linear quadrupole ion trap (LQIT) equipped with an atmospheric pressure chemical ionization (APCI) source. (+)APCI/CS2 was used to generate stable dominant molecular ions for all the compounds studied except for three sulfides that also showed abundant fragment ions. The LQIT coupled with an orbitrap mass spectrometer was used for elemental composition analysis, which facilitated the identification of the neutral molecules lost during fragmentation. RESULTS: The characteristic fragment ions generated in MS 2 and MS 3 experiments provide clues for the chemical bonding environment of sulfur atoms in the examined compounds. Upon collision‐induced dissociation (CID), the molecular ions can lose the sulfur atom in a variety of ways, including as S (32 Da), HS (33 Da), H2 S (34 Da), CS (44 Da), CHS (45 Da) and CH2 S (46 Da). These neutral fragments are not only indicative of the presence of sulfur, but also of the type of sulfur present in the compound. Generally, losses of HS and H2 S were found to be associated with compounds containing saturated sulfur functionalities, while losses of S, CS and CHS were more common for heteroaromatic sulfur compounds. CONCLUSIONS: High‐resolution tandem mass spectrometry with APCI/CS2 ionization is a viable approach to determining the types of organosulfur compounds. It can potentially be applied to analysis of complex mixtures, which is beneficial to improving the desulfurization process of fossil fuels. Copyright © 2016 John Wiley & Sons, Ltd.